PARC: a phase I/II study evaluating the safety and activity of pegylated recombinant human arginase BCT-100 in relapsed/refractory cancers of children and young adults - Fenwick, Nicola; Weston, Rebekah; Wheatley, Keith; Hodgson, Jodie; Marshall, Lynley; Elliott, Martin; Makin, Guy; Ng, Antony; Brennan, Bernadette; Lowis, Stephen; Adamski, Jenny; Kilday, John Paul; et al. (Frontiers in Oncology, 2024)
Background: The survival for many children with relapsed/ refractory cancers remains poor despite advances in therapies. Arginine metabolism plays a key role in the pathophysiology of a number of paediatric cancers. We report the first in child study of a recombinant human arginase, BCT-100, in children with relapsed/refractory haematological, solid or CNS cancers. Procedure: PARC was a single arm, Phase I/II, international, open label study. BCT-100 was given intravenously over one hour at weekly intervals. The Phase I section utilised a modified 3+3 design where escalation/de-escalation was based on both the safety profile and the complete depletion of arginine (defined as adequate arginine depletion; AAD <8μM arginine in the blood after 4 doses of BCT-100). The Phase II section was designed to further evaluate the clinical activity of BCT-100 at the paediatric RP2D determined in the Phase I section, by recruitment of patients with paediatric cancers into 4 individual groups. A primary evaluation of response was conducted at eight weeks with patients continuing to receive treatment until disease progression or unacceptable toxicity. Results: 49 children were recruited globally. The Phase I cohort of the trial established the Recommended Phase II Dose of 1600U/kg iv weekly in children, matching that of adults. BCT-100 was very well tolerated. No responses defined as a CR, CRi or PR were seen in any cohort within the defined 8 week primary evaluation period. However a number of these relapsed/refractory patients experienced prolonged radiological SD. Conclusions: Arginine depletion is a clinically safe and achievable strategy in children with cancer. The RP2D of BCT-100 in children with relapsed/refractory cancers is established at 1600U/kg intravenously weekly and can lead to sustained disease stability in this hard to treat population.